2021
DOI: 10.1159/000517326
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Oncological Outcome and Prognostic Analysis in a First-Line Setting of Short Hydration Gemcitabine and Cisplatin Chemotherapy for Patients with Metastatic Urothelial Carcinoma

Abstract: <b><i>Objectives:</i></b> The aim of the study was to examine the effectiveness of a modified-short hydration gemcitabine and cisplatin (m-shGC) regimen for patients with metastatic urothelial carcinoma (mUC) and to assess the efficacy of a geriatric nutritional risk index (GNRI) with regard to prognosis. <b><i>Patients and Methods:</i></b> From January 2016 to July 2020, 68 patients with mUC underwent first-line m-shGC therapy with 70 mg/m<sup>2</sup>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Table 1 shows the typical characteristics of the included studies. The articles considered were published in full-text format in the English language between 2015 and 2022 (14)(15)(16)(17)(18)(19)(20)(21). Four studies were performed in Japan (15,16,19,21), two in China (14,20), and one each in Korea (17) and Taiwan (18).…”
Section: Features Of the Included Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 shows the typical characteristics of the included studies. The articles considered were published in full-text format in the English language between 2015 and 2022 (14)(15)(16)(17)(18)(19)(20)(21). Four studies were performed in Japan (15,16,19,21), two in China (14,20), and one each in Korea (17) and Taiwan (18).…”
Section: Features Of the Included Researchmentioning
confidence: 99%
“…The articles considered were published in full-text format in the English language between 2015 and 2022 (14)(15)(16)(17)(18)(19)(20)(21). Four studies were performed in Japan (15,16,19,21), two in China (14,20), and one each in Korea (17) and Taiwan (18). The sample sizes ranged from 68 to 4,591, with a median of 319.5.…”
Section: Features Of the Included Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Systemic inflammation, which can detrimentally affect solid tumors, is measured by assessing peripheral blood [19][20][21][22][23]. Numerous studies have identified serum biomarkers associated with oncological outcomes in patients with metastatic or localized bladder cancer receiving systemic chemotherapy [24,25] or radical treatment [26,27]. Of such prognostic markers, the modified Glasgow prognostic score (mGPS) is used to assess nutrition and is convenient and easy to use since it is based on C-reactive protein (CRP) and serum albumin (Alb) levels [28].…”
Section: Introductionmentioning
confidence: 99%